GAYA DIRECT CINEMA PADA PENYUTRADARAAN FILM DOKUMENTER DI BALIK DONGENG KANCIL - Prasojo, Satriyo Bagus; R., Cito Yasuki (Seni Media Rekam ISI Surakarta, 2015)
The documentary film entitled Di Balik Dongeng Si Kancil tells about high dedication and awareness of an artist named Ki Ledjar Subroto in the development of pewayangan (shadow puppet) at once as an environmental conservationist. Wayang Kancilwas used to develop and find out strategies to educate young generation especially children in the way of how to understand the wayang. Wayang Kancil is a kind of wayang which can also be used as education medium in understanding and conserving environment. This creating used concept of â€œdirect cinemaâ€ in producing documentary film entitled DiBalik Dongeng Kancil. The film shows wayang medium can be used as learning medium. Film recording emphasized actions spontaneously and naturally to impress proximity between subjects and audiences. Structure and narrative aspects in conveying information in this documentary film expressed using linear pattern through visual dialog of the subjects or informants, while narration by narrator is not emerged. Therefore, the visualization of the subjects in the interview constitutes an important part in describing information in every scene or event in this documentary film about the importance of conserving Indonesian culture.Keywords: Wayangkancil, documentary, film, and direct cinema